2018
DOI: 10.1080/17429145.2018.1466373
|View full text |Cite
|
Sign up to set email alerts
|

Activity of defense related enzymes and gene expression in pigeon pea (Cajanus cajan) due to feeding of Helicoverpa armigera larvae

Abstract: The biochemical and molecular basis of the defense in a mild tolerant (ICPL-332) and susceptible (ICPL-87) cultivars of pigeon pea (Cajanus cajan) due to Helicoverpa. armigera infestation was studied. We found that feeding by the larvae generated H 2 O 2 in a localized manner and activity was observed upto 12 h (hrs) of with a sharp decline within 24 h. Similarly, PPO activity was also detected till 12 h of treatment, which decreased after 24 h of feeding by larvae. The activity of trypsin inhibitor was detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 77 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…This defence mechanism contributes to the enhanced tolerance of the wild pigeonpea in response to any form of tissue damage. Meitei et al [ 32 ] observed similar results on DAB staining on pigeonpea leaves where the tolerant pigeonpea leaves of ICPL 332 had darker DAB staining when compared with the leaves of the susceptible ICPL 87 indicating more accumulation of ROS in ICPL 332. Orozco–Cardenas and Ryan, [ 33 ] also observed that tolerant tomato had darker DAB staining compared to susceptible tomato.…”
Section: Discussionmentioning
confidence: 75%
“…This defence mechanism contributes to the enhanced tolerance of the wild pigeonpea in response to any form of tissue damage. Meitei et al [ 32 ] observed similar results on DAB staining on pigeonpea leaves where the tolerant pigeonpea leaves of ICPL 332 had darker DAB staining when compared with the leaves of the susceptible ICPL 87 indicating more accumulation of ROS in ICPL 332. Orozco–Cardenas and Ryan, [ 33 ] also observed that tolerant tomato had darker DAB staining compared to susceptible tomato.…”
Section: Discussionmentioning
confidence: 75%
“…Phenols constitute one of the most common, important and extensively studied groups of compounds with a major role in providing resistance (Sharma et al, 2009;War et al, 2013;War et al, 2015). They act as first line of defense by reduction of reactive oxygen species (ROS) produced as a result of insect herbivory ultimately leading to the activation of defensive enzymes (Maffei et al, 2007;Meitei et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…After boiling for 3 h in a fixative solution comprising ethanol and acetic acid in a 3:1 ratio, the stained leaf samples were incubated for 1 h in lacto-glycerol solution (lactic acid/glycerol/water, 1:1:1). The leaf samples were kept in microscopic slides and photographed [52]. The presence of H 2 O 2 /mm 2 from WT (control) and CRISPR-edited necrotic leaves was quantified by using Image J software [42].…”
Section: Detection Of Hydrogen Peroxide (H 2 O 2 )mentioning
confidence: 99%